PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING FINANCE, DAN NET INTEREST MARGIN TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH - Ni Made Priska Setiawati; I Wayan Widnyana; I Gusti Ngurah Bagus Gunadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Islamic Bank or hereinafter referred to as Islamic Bank, is a Bank that operates without relying on interest. An Islamic bank or commonly referred to as an interest-free bank, is an operational financial/banking institution. The emergence of Islamic banks is not only a financial intermediary (financial intermediary), but also revolutionized with real participation in the business world and mobilizing in funding. The funding revolution can be proven by the principle of profit and loss (profit and loss sharing) which is different from conventional interest-based banks. This study aims to examine the effect of Capital Adequacy Ratio (CAR), Non Performing Finance (NPF), and Net Interest Margin (NIM) on Profitability in Islamic Commercial Banks. The research population is Islamic Commercial Bank companies in Indonesia which are listed on the Indonesia Stock Exchange in 2015-2019. The sample in this study was 19 Islamic commercial banks which were determined based on the purposive sampling method. The analytical tool used to test the hypothesis is multiple linear regression analysis. The results showed that the Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) had a positive and significant effect on profitability. Meanwhile, Non-Performing Finance (NPF) has a negative and insignificant effect on profitability. Further research can develop this research by using other variables to determine the effect of each new variable used for further research.